Economic evaluation of the Good School Toolkit: an intervention for reducing violence in primary schools in Uganda. Issue 2 (17th April 2018) - Greco, Giulia; Knight, Louise; Ssekadde, Willington; Namy, Sophie; Naker, Dipak; Devries, Karen
Abstract : Introduction: This paper presents the cost and cost-effectiveness of the Good School Toolkit (GST), a programme aimed at reducing physical violence perpetrated by school staff to students in Uganda. Methods: The effectiveness of the Toolkit was tested with a cluster randomised controlled trial in 42 primary schools in Luwero District, Uganda. A full economic costing evaluation and cost-effectiveness analysis were conducted alongside the trial. Both financial and economic costs were collected retrospectively from the provider's perspective to estimate total and unit costs. Results: The total cost of setting up and running the Toolkit over the 18-month trial period is estimated at US$397 233, excluding process monitor (M&E) activities. The cost to run the intervention is US$7429 per school annually, or US$15 per primary school pupil annually, in the trial intervention schools. It is estimated that the intervention has averted 1620 cases of past-week physical violence during the 18-month implementation period. The total cost per case of violence averted is US$244, and the annual implementation cost is US$96 per case averted during the trial. Conclusions: The GST is a cost-effective intervention for reducing violence against pupils in primary schools in Uganda. It compares favourably against other violence reduction interventions in the region.